(untitled) (Eurasian Journal of Humanities and Social Sciences, 2026)
This article discusses the scientific and practical foundations of optimizing cadastral documents and the requirements imposed on them. The role of cadastral documentation in land management, real estate registration, urban planning, and property relations is analyzed. Modern approaches to the optimization of cadastral systems, including digital technologies, geographic information systems (GIS), electronic databases, and automated cadastral management systems, are scientifically substantiated. In addition, the legal, technical, and informational requirements for cadastral documents, as well as their importance in ensuring transparency, accuracy, and efficiency in land administration, are highlighted.